Biotechnological research in Ukraine for solving energy, medical-biological and medicalecological problems in 2009-2015 taking into account the implementation of the association agreement with the EU - Igor Yu. Matyushenko; Iryna An. Sviatukha; Marina S. Loktionova (ACTA INNOVATIONS, 2018)
This article summarizes the main results of the biotechnological research of the National Academy of Sciences of Ukraine aimed at solving energy, medical-biological and medical-ecological problems during the period from 2009 to 2015. The prospective bioresources and directions of implementation of the latest technologies of bioenergy conversion for the production of liquid biofuels and expansion of their use for biodiesel were determined. The latest medical and biological and bioengineering technologies for human health and the national economy, biologically active substances for human health, ecological and economic mechanisms of rational use, protection and monitoring of natural resources, new technologies for the efficient use of energy resources were presented in the article. The authors systematized the results of the current research of the National Academy of Science of Ukraine aimed at the development of modern methods for the prevention and diagnosis of diseases in humans and animals, modern methods of cell biotechnology and metabolic engineering for the creation of superproducts of biologically active substances, new forms of plants and microorganisms, the genetic design of improved microorganisms and lines of plant and animal cells for the development of medical and agricultural biotechnology. The authors proved that these directions of research fully correspond to the world-wide trends in research in biomedicine.